Family Issues in the Socio-Philosophical Views of Abu Rayhan Biruni (The Peerian Journal, 2022)
The article discusses the issues of family and family education, ethics in the sociophilosophical views of Abu Rayhon Beruni, and also discusses the importance of educating a harmonious personality in our days.